HUKUM MODERN DAN PROSES PENAKLUKAN - Faisal, Faisal (Fakultas Hukum Universitas Bangka Belitung, 2016)
Scientific of modern law is strongly influenced by the emergence of the paradigm of positivism. Modern law which in various ways or road, then spread to various parts of the world, is a type of law reached the peak of its development in the 19th century in Europe. The influence of modern law can make local laws with all their local wisdom becomes alienated in your own home. This is done by a process of conquest.